Caboclos da Serra do Botucaraí : cultura, economia e sociabilidades - Pinto, Jane Cunha (2022)
Caboclos are the core of Brazilian identity. They are present from north to south of the country and ethnically correspond to a mixture that occurred between Portuguese and Indians, Portuguese and Black People, or even the union of Indians and Black People. Culturally, some common characteristics of this social group are the strong link with nature, the condition of poverty, the possession or property of small areas of land where they practice subsistence agriculture, the community relations full of meaning about family members, godfathers, neighbors and the forms of religiosity that transit between Catholic formalism and religious syncretism. From this, this work aims to promote the understanding of the caboclo individual, being at the macro level, from the representations attributed to him in the different spaces in which he moves, or at the micro level, in understanding the locus of research. The research problem aims to identify the profile of the caboclo that is present in the northwest region of the State of RS, specifically in the Alto da Serra do Botucaraí region, Fontoura Xavier town, involving aspects such as land ownership; ethnicity; living conditions that are present; the way of occupations; the continued or temporary migration to obtain the means of life; the forms of food and leisure; the family relationship and with neighbors and godfathers; the female representation; the relationship with the land and aspects of religiosity. This research is justified by the socially relevant importance of getting to know the caboclo more deeply, that is present in the extreme south of the country, as a way to better understand the crossings and adjustments of this population. The oral history methodology, through semi-structured interviews with the subjects, was used to answer the research problem, contributing to a better understanding of the profiles and the caboclos life path. Such individuals are housed in geographically composed areas of forests and in mountainous lands, where in the small useful areas of their properties they practice subsistence agriculture, tobacco and mate herb cultivation. They practice continuous migrations to urban centers to pursue other professional activities and make a living. Locally, they work continuously or seasonally as mate herb workers.